Determinant Factors for Knowledge Sharing in Facilities Management of Private Finance Initiative Procurement - Irwan Mohammad Ali; Mohd Azian Zaidi; Kharizam Ismail; Mohamed Imran Mohamed Ariff (International Journal of Supply Chain Management, 2018)
In the current state of Private Finance Initiative (PFI) procurement, there are numerous problems and issues stressed out by some scholars. The case is more complicated and critical once the PFI procurement come to Facilities Management (FM) phase. By means of accepting the contribution of Knowledge Sharing (KS) towards organizational performance, a cross sectional study design was conducted. This research aims are to identify the determinant factors towards knowledge sharing in facilities management of private finance initiative procurement. A set of questionnaires was developed based on numerous constructs gained from previous studies. A total of 50 set web-based self-administrative questionnaire were distributed amongst FM and PFI procurement experts. However, only 39 sets were answered and completed. The data then analyses using SPSS Statistics Version 21. The finding suggested the conceptual framework for this research consists of five determinant factors as independent variables working culture, staff attitude, motivation to share, nature of knowledge to share, and opportunities to share. Meanwhile, knowledge sharing benefits towards performance management as dependent variables.